2017
DOI: 10.1111/mec.14046
|View full text |Cite
|
Sign up to set email alerts
|

Unusual evolutionary mechanisms to escape effector‐triggered immunity in the fungal phytopathogen Leptosphaeria maculans

Abstract: Leptosphaeria maculans is the fungus responsible for the stem canker disease of oilseed rape (Brassica napus). AvrLm3 and AvrLm4-7, two avirulence effector genes of L. maculans, are involved in an unusual relationship: AvrLm4-7 suppresses the Rlm3-mediated resistance. Here, we assessed AvrLm3 polymorphism in a collection of 235 L. maculans isolates. No field isolates exhibited deletion or inactivating mutations in AvrLm3, as observed for other L. maculans avirulence genes. Eleven isoforms of the AvrLm3 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 61 publications
5
53
0
Order By: Relevance
“…A hide and seek relationship between AvrLm3 and AvrLm4-7 was reported by Plissonneau et al (2016), where L. maculans isolates carrying AvrLm4-7 also carried AvrLm3 (but the function of AvrLm3 was blocked by AvrLm4-7). A very recent paper by Plissonneau et al (2017) demonstrated the "camouflaged model," where the loss of Rlm3-mediated resistance response in isolates virulent toward Rlm3 occurred by two methods. The first method was through deletion or inactivation mutations of AvrLm4-7, which resulted in virulent isoforms of the AvrLm3 protein.…”
Section: Discussionmentioning
confidence: 99%
“…A hide and seek relationship between AvrLm3 and AvrLm4-7 was reported by Plissonneau et al (2016), where L. maculans isolates carrying AvrLm4-7 also carried AvrLm3 (but the function of AvrLm3 was blocked by AvrLm4-7). A very recent paper by Plissonneau et al (2017) demonstrated the "camouflaged model," where the loss of Rlm3-mediated resistance response in isolates virulent toward Rlm3 occurred by two methods. The first method was through deletion or inactivation mutations of AvrLm4-7, which resulted in virulent isoforms of the AvrLm3 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Another unusual particularity of the AvrLm10A-AvrLm10B pair lies in its effect on lesion size. Until now, all three tested L. maculans avirulence genes have been shown to promote lesion development (Huang et al, 2010;Nov akov a et al, 2016;Plissonneau et al, 2017). Isogenic lines or isolates complemented with the avirulence gene induced larger lesions than those in which the gene was absent.…”
Section: Donormentioning
confidence: 99%
“…1). Recently reported examples include SNPs (Lu et al, 2016;Plissonneau et al, 2017b;Zhong et al, 2017;Meile et al, 2018), deletions , transposable element (TE) insertions (Wu et al, 2015;Zhang et al, 2015), and epigenetic gene silencing (Qutob et al, 2013) of avirulence genes, all of which can result in a gain of virulence. An instance of great agronomical relevance is the emergence of the rice blast fungus as a novel pathogen of wheat that was promoted by the loss of the critical PWT3 Avr gene (Inoue et al, 2017).…”
Section: Loss Of Avirulence: a Frequent Type Of Rapid Evolutionarmentioning
confidence: 99%